2020
DOI: 10.47627/gradus.v5i1.149
|View full text |Cite
|
Sign up to set email alerts
|

perception and comprehension of L2 English sentence types

Abstract: L2 prosody is particularly difficult to acquire, because it requires an understanding of intonation, syntax, and pragmatics. For example, to acquire English sentence types, speakers must learn that statements (Ss) and absolute yes/no questions (AQs) are syntactically and prosodically marked, whereas the difference between Ss and declarative questions (DQs) is purely prosodic. Moreover, DQs can only occur in restricted contexts, such as to express surprise. In this paper, we examine the L2 perception and compre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…These studies, however, did not explore whether access to contextual information was responsible for the differences observed. Studies that have examined the role of access to contextual information have yielded consistent results both in perception (Grabe et al 2003;Radu et al 2018;Patience et al 2020) and perception-production (Ortega-Llebaria and Colantoni 2014). Grabe et al's (2003) pioneering study showed that three groups of English, Mandarin and Peninsular Spanish speakers did not differ in their discrimination of falling and rising contours in non-speech stimuli (i.e., frequency modulated sine-waves), but differed in their perception of falling contours when they listened to the utterance Melanie Maloney (whose final syllable was manipulated to generate 11 different stimuli with rising and falling contours) produced by a Scottish English speaker.…”
Section: Role Of Task Type In Modulating CLI In Contact Situationsmentioning
confidence: 86%
See 3 more Smart Citations
“…These studies, however, did not explore whether access to contextual information was responsible for the differences observed. Studies that have examined the role of access to contextual information have yielded consistent results both in perception (Grabe et al 2003;Radu et al 2018;Patience et al 2020) and perception-production (Ortega-Llebaria and Colantoni 2014). Grabe et al's (2003) pioneering study showed that three groups of English, Mandarin and Peninsular Spanish speakers did not differ in their discrimination of falling and rising contours in non-speech stimuli (i.e., frequency modulated sine-waves), but differed in their perception of falling contours when they listened to the utterance Melanie Maloney (whose final syllable was manipulated to generate 11 different stimuli with rising and falling contours) produced by a Scottish English speaker.…”
Section: Role Of Task Type In Modulating CLI In Contact Situationsmentioning
confidence: 86%
“…CLI was restricted to the interpretation of the different question types (see Section 2.2). Finally, Patience et al (2020) found that L1 Mandarin speakers could use intonation to identify questions from statements in a low-pass filtered task; however, when the statements were presented as isolated utterances (not low-pass filtered), the L1 Mandarin speakers had difficulty distinguishing between Ss and DQs, suggesting that they paid more attention to the syntax than the intonation. The authors interpreted this as evidence of CLI, given that Mandarin yes-no questions are marked more reliably with syntax than with prosody.…”
Section: Cross-linguistic Influence and Sentence Typesmentioning
confidence: 96%
See 2 more Smart Citations